CREATING ACTIVITIES FOR TEACHING READING TO YOUNG LEARNERS. - Eshniyozova Jasmina Jo’rabekovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This paper provides a comprehensive overview of activities that promote the development of reading skills in young learners. Focusing on interactive and hands-on methods, it suggests various strategies that engage children in the reading process. Through activities like story mapping, letter and word hunts, rhyming games, and sequencing, the paper demonstrates how educators can help young students build essential skills such as vocabulary recognition, comprehension, and phonological awareness. The study emphasizes the importance of repetition and visual support, which are key to developing reading fluency. It also discusses the significance of creating a fun and stimulating environment to motivate children in their literacy journey, fostering a love of reading at an early age.